ASSESSING THE IMPACT OF THE FARM ROAD PROGRAM ON REDUCING OPERATIONAL COSTS FOR PEPPER FARMERS IN PURBALINGGA REGENCY - Bayu Mahendra, (Juremi: Jurnal Riset Ekonomi, 2025)
This study examines the impact of the Farm Road Program on reducing operational costs for pepper farmers in Purbalingga Regency, Indonesia. The program, a government initiative, was designed to enhance agricultural efficiency by constructing new roads in agricultural areas across 14 districts. These farm roads aim to facilitate better access to markets, inputs, and other essential services, ultimately reducing transportation time and costs for farmers. A key novelty of this research is the inclusion of government policy specifically the program as a variable influencing the operational costs of pepper farming. This study quantitatively evaluates the impact of the program on pepper farmers’ expenses. Based on data collected from participating pepper farmers, the findings reveal that the program successfully reduced operational costs by IDR 913,333, representing a 22% decrease compared to pre-program costs. The analysis employed a paired t-test to determine the statistical significance of this reduction. The results of the t-test showed a p-value of less than 0.005 (p = 0.000), indicating that the reduction in operational costs is statistically significant. This finding confirms the effectiveness of the program in achieving its intended goal of reducing farmers’ costs and improving their overall agricultural efficiency.In conclusion, the program demonstrates its value as an effective government policy intervention for enhancing the financial sustainability of pepper farmers by lowering operational costs and promoting more efficient farming practices.